2012
DOI: 10.2119/molmed.2012.00131
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Signaling Pathway Is Involved in Renal Fibrosis by Favoring a TH2 Immune Response and Activating Alternative M2 Macrophages

Abstract: Inflammation contributes to the pathogenesis of chronic kidney disease (CKD). Molecules released by the inflamed injured tissue can activate toll-like receptors (TLRs), thereby modulating macrophage and CD4(+) T-cell activity. We propose that in renal fibrogenesis, M2 macrophages are recruited and activated in a T helper subset 2 cell (T(H)2)-prone inflammatory milieu in a MyD88-dependent manner. Mice submitted to unilateral ureteral ligation (UUO) demonstrated an increase in macrophage infiltration with colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…In this sense, it is feasible to suggest that the immune cells might be responsible, at least in part, for this injury. The involvement of macrophages infiltration in the renal tissue after an insult was already detected in different works [5, 12]. Several groups have attributed reduced morphologic kidney damage when macrophages were depleted in different experimental models [13, 14].…”
Section: Discussionmentioning
confidence: 96%
“…In this sense, it is feasible to suggest that the immune cells might be responsible, at least in part, for this injury. The involvement of macrophages infiltration in the renal tissue after an insult was already detected in different works [5, 12]. Several groups have attributed reduced morphologic kidney damage when macrophages were depleted in different experimental models [13, 14].…”
Section: Discussionmentioning
confidence: 96%
“…Others have shown that, 7 days after unilateral ureteral obstruction (UUO), TLR4 knock-out mice have decreased renal fibrosis of the obstructed kidney and decreased proteinuria in urine collected from the unobstructed kidney in comparison to WT mice (Braga et al. 2012). Similarly, in an adenine-induced tubulointerstitial fibrosis model, TLR4 knock-out mice are protected from interstitial fibrosis and increases in serum creatinine (Correa-Costa et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010), shifting the balance between M1:M2 macrophage responses (Braga et al. 2012), and fibroblast accumulation (Campbell et al. 2011) during renal fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that absence of TLR2 decreased the synthesis of type I collagen [30]. These differences among the studies could be explained by the fact that fibroblasts from different anatomic locations differ markedly in their gene expression patterns and show site-specific variations in their transcriptional profiles that seem to be related to their location within the body [31].…”
Section: Discussionmentioning
confidence: 99%